The Signature of Maternal Rearing in the Methylome in Rhesus Macaque Prefrontal Cortex and T Cells - Provençal, Nadine (Society for Neuroscience, 2012)
Early-life adversity is associated with a broad scope of life-long health and behavioral disorders. Particularly critical is the role of the mother. A possible mechanism is that these effects are mediated by “epigenetic” mechanisms. Studies in rodents suggest a causal relationship between early-life adversity and changes in DNA methylation in several “candidate genes” in the brain. This study examines whether randomized differential rearing (maternal vs surrogate–peer rearing) of rhesus macaques is associated with differential methylation in early adulthood. The data presented here show that differential rearing leads to differential DNA methylation in both prefrontal cortex and T cells. These differentially methylated promoters tend to cluster by both chromosomal region and gene function. The broad impact of maternal rearing on DNA methylation in both the brain and T cells supports the hypothesis that the response to early-life adversity is system-wide and genome-wide and persists to adulthood. Our data also point to the feasibility of studying the impact of the social environment in peripheral T-cell DNA methylation.